Governance, Health Financing and Health Outcomes in Nigeria: A Quantitative Assessment - Akintunde, Temitope Sade; Adesina, Kehinde Elizabeth; Akinrinde, Olawale Olufemi (International Studies. Interdisciplinary Political and Cultural Journal, 2024)
Good health is essential to achieve sustainable development in any economy. Nigeria is no exception. No wonder it is the third goal in the sustainable development goals of the United Nations. Achieving good health also needs to be well funded with institutional quality, hence this study. This paper examined the effect of health financing and governance quality on health outcomes in Nigeria from 1980 to 2018 using secondary data sourced from World Development Indicators (WDI). A co-integration test and a vector error correction model (VECM) were employed to analyse the data. Short- and long-term results of an analysis based on life expectancy and infant mortality as a measure of health outcomes and dependent variables demonstrate that institutions empowered with good governance could produce positive health outcomes in the country.